Toleransi; Keharusan Sosial Ataukah Kewajiban Agama (Sudut Pandang Islam Dalam Konteks Keindonesiaan) - Amrullah Amrullah; Mulyadi Bin Jailani (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2021)
Every religion teaches the values of tolerance and longing for peace. Islam as a concept of tolerance for differences is called social necessity in the reality of religious diversity, because in the concept of social necessity, there are values of love, wisdom (wisdom), universal benefit, and justice. The question is, is tolerance a religious obligation or a social imperative? This study uses a qualitative methodology with a normative approach. The findings in this study indicate that tolerance in this context is viewed from several aspects, namely theological, sociological and cultural. With tolerance, it is hoped that humans will be able to recognize diversity, including religious diversity, which is called pluralism. In addition to tolerance and pluralism, the concept of religious dialogue is also present to create such harmony, as Islam exemplifies with the example of Muhammad SAW as a prophet while in Medina who protected every citizen, both Muslim and non-Muslim from his enemies, so that the Medina charter was created.